2020
DOI: 10.3390/antiox9020169
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic and Anthocyanin Compounds and Antioxidant Activity of Tamarillo (Solanum betaceum Cav.)

Abstract: This study examined phenolics and anthocyanins present in Amber, Laird’s Large and Mulligan cultivars of tamarillo that were cultivated in Whangarei, Northland of New Zealand. Samples were further separated by their tissue types, peel and pulp. Using LC-MS/MS, twelve polyphenols were quantified and six (ellagic acid, rutin, catechin, epicatechin, kaempferol-3-rutinoside and isorhamnetin-3-rutinoside) were detected for the first time in tamarillo. Mulligan cultivar showed the highest amounts of phenolic and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 60 publications
5
59
4
1
Order By: Relevance
“…Also, during the lipid peroxidation and inhibition of inflammation, a synergetic interaction between ascorbic acid and α-tocopherol has been reported [ 7 ]. High contents of vitamin C, α-tocopherol (from current study) and rutin (from another study [ 23 ]) have been observed in tamarillo, therefore, further research should be conducted to investigate synergetic effect of vitamin C-rutin and vitamin C-α-tocopherol in tamarillo.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Also, during the lipid peroxidation and inhibition of inflammation, a synergetic interaction between ascorbic acid and α-tocopherol has been reported [ 7 ]. High contents of vitamin C, α-tocopherol (from current study) and rutin (from another study [ 23 ]) have been observed in tamarillo, therefore, further research should be conducted to investigate synergetic effect of vitamin C-rutin and vitamin C-α-tocopherol in tamarillo.…”
Section: Discussionmentioning
confidence: 77%
“…Tamarillos are good sources of dietary fiber, vitamins A, C, and E, as well as some minerals, carotenoids and anthocyanins [14,16,17]. Several studies have attempted to explore proximate compositions [16,18], sugars and organic acids [14,19], pigments [20][21][22], phenolics and anthocyanins [23], carotenoids [20,24,25], vitamins [16,26] and minerals [27] in tamarillos. These studies have focused on the pulp of the tamarillo, with exclusion of peels.…”
Section: Introductionmentioning
confidence: 99%
“…cerasiforme 40 , Dioscorea alata 41, 42 , Litsea quinqueflora 43 , Solanum betaceum 44 , Morus spp. 45 and in other fruits and vegetables 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The addition of antioxidants can inhibit lipid peroxidation reactions (Ayala et al, 2014). Solanum betaceum is a fruit that contains quite high natural antioxidants such as anthocyanins, flavonoids, carotenoids, tannins, and saponins (Diep et al, 2020;Khaerunnisa et al, 2019). High antioxidants can reduce lead-induced oxidative stress in experimental animals (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%